CHILDREN’S RIGHTS: FROM ANTIQUITY TO CONTEMPORARY INTERNATIONAL STANDARDS - Sultonov Nodirbek (Scholar Express Journals, 2025)
This article analyzes the emergence of the concept of children's rights, stages of historical development, and modern international legal foundations. The article also substantiates how the legal status of children changed, starting with Roman and Greek societies, through important historical events such as the Renaissance, the Industrial Revolution of the 19th and 20th centuries, and the Universal Declaration of Human Rights
Keywords: Children's rights; convention; declaration